The ASi–Sii Defect Model of Light‐Induced Degradation (LID) in Silicon: A Discussion and Review. Issue 19 (16th August 2022) - Lauer, Kevin; Peh, Katharina; Schulze, Dirk; Ortlepp, Thomas; Runge, Erich; Krischok, Stefan
Abstract : The A Si –Si i defect model as one possible explanation for light‐induced degradation (LID) in typically boron‐doped silicon solar cells, detectors, and related systems is discussed and reviewed. Starting from the basic experiments which led to the A Si –Si i defect model, the A Si –Si i defect model (A: boron, or indium) is explained and contrasted to the assumption of a fast‐diffusing so‐called "boron interstitial." An LID cycle of illumination and annealing is discussed within the conceptual frame of the A Si –Si i defect model. The dependence of the LID defect density on the interstitial oxygen concentration is explained within the A Si –Si i defect picture. By comparison of electron paramagnetic resonance data and minority carrier lifetime data related to the assumed fast diffusion of the "boron interstitial" and the annihilation of the fast LID component, respectively, the characteristic EPR signal Si‐G28 in boron‐doped silicon is related to a specific A Si –Si i defect state. Several other LID‐related experiments are found to be consistent with an interpretation by an A Si –Si i defect. Abstract : A Si –Si i defect model of light‐induced degradation (LID) in silicon for solar cells and detectors is discussed and reviewed. LID cycle is explained within the A Si –Si i defect model by basic experiments (carrier lifetime and photoluminescence line). Implications related to the dependence of the LID defect density on the interstitial oxygen concentration and the so‐called "boron interstitial" are critically discussed.